The effect of certified herbal medicines non - inclusion in the national health insurance scheme (NHIS) on health care delivery within the Kumasi metropolis - Nketia, Anthony (2021)
A thesis submitted to the Department of Health Education, Promotion and Disability, School of Public Health, College of Health Sciences, in partial fulfillment of the requirements for the Award of the Degree of Master of Public Health in Health Promotion and Education.